Role of conventional magnetic resonance imaging and diffusion-weighted imaging in evaluation of breast lesions - Mohammed Abdel-Fattah; Hoda Abdel-Kareem; Yasser Abdel-Aal Ahmed; Moutaz Mahmoud Sleem (Wolters Kluwer Medknow Publications, 2021)
Background and Aim This study aimed to evaluate the role of diffusion-weighted imaging (DWI) and apparent diffusion coefficient in diagnosis of the breast lesions. Patients and methods This study included 100 patients referred to the Radiology Department of Al-Azhar Assiut University Hospital from February 2018 to May 2020 for DWI MRI examination with a provisional diagnosis of breast lesions. All patients were recruited after meeting the inclusion criteria. They underwent clinical examination, mammography, ultrasonography, and contrast-enhanced MRI with DWI. Results Our study included 100 cases. The combined MRI protocol of dynamic contrast-enhanced (DCE)-MRI and DWI was true positive in 60 and true negative in 30 patients. The combined MRI protocol of DCE-MRI and DWI provided a sensitivity of 92%, a specificity of 90%, a positive predictive value of 95.8%, a negative predictive value of 81.8% and accuracy of 91.43%. In this study, the addition of DWI to standard DCE-MRI provided a 10% increase in the specificity of breast MRI, with a 4% decrease in the sensitivity. Conclusion DWI is a short unenhanced scan and had the highest specificity compared with other imaging modalities, as it reduced the false-positive results. It should be added to conventional breast MRI to increase the sensitivity and specificity of MRI.